Perkembangan Pesantren di Indonesia (Era Orde Lama, Orde Baru, Reformasi) - Hamzah, Syeh Hawib (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
Boarding school as the oldest educational institutions in Indonesia have a significant contribution to the Muslims in Indonesia , even up to the nation . Since the beginning of the coming of Islam to the era reform schools still exist and can keep abreast advances in science and technology , so that the boarding school be a great hope for this nation to relaese candidat the best to participate in the development and progress of the nation in various eras